Clinical outcomes among adolescents living with HIV in Kenya following initiation on antiretroviral treatment. - Judith Kose; Appolinaire Tiam; Stephen Siamba; Cosima Lenz; Elizabeth Okoth; Theresa Wolters; David van de Vijver; Natella Rakhmanina (Public Library of Science (PLoS), 2022)
In Kenya, HIV/AIDS remains a leading cause of morbidity and mortality among adolescents living with HIV (ALHIV). Our study evaluated associations between demographic and healthcare factors and HIV treatment outcomes among ALHIV in care in Kenya. This retrospective cohort study evaluated the clinical outcomes of newly diagnosed ALHIV enrolled in HIV care during January 2017-June 2018 at 32 healthcare facilities in Homabay and Kakamega Counties. Demographic and clinical data were abstracted from patient clinical records and registers during the follow up study period January 2017-through May 2019. ALHIV were stratified by age (10-14 versus 15-19 years). Categorical variables were summarized using descriptive statistics; continuous variables were analyzed using mean values. The latest available treatment and virological outcomes for ALHIV were assessed. 330 ALHIV were included in the study (mean age 15.9 years; 81.8% female, 63.0% receiving HIV care at lower-level healthcare facilities). Most (93.2%) were initiated on ART within 14 days of diagnosis; 91.4% initiated EFV-based regimens. Of those on ART, only 44.6% were active on care at the end of the study period. Of those eligible for viral load testing, 83.9% were tested with 84.4% viral suppression rate. Retention in care was higher at higher-level facilities (67.5%) compared to lower-level facilities (28.6%). Factors associated with higher retention in care were school attendance (aRR = 1.453), receipt of disclosure support (aRR = 13.315), and receiving care at a high-level health facility (aRR = 0.751). Factors associated with viral suppression included older age (15-19 years) (aRR = 1.249) and pre-ART clinical WHO stage I/II (RR = .668). Viral suppression was higher among older ALHIV. Studies are needed to evaluate effective interventions to improve outcomes among ALHIV in Kenya.